Perovskite-type oxide-based dual composite cathode for solid oxide fuel cells: a short review - Abdul Rahman, Nurul Farhana; Abd.Rahman, Hamimah; Azmi, Mohd Azham (Trans Tech Publications, 2021)
A fuel cell is an electrochemical device that provides efficient power generation. Solid fuel oxide cell (SOFC) is an electrochemical device that generates electrical energy and heat from the gaseous state of fuel using an oxidant. SOFC is a highly efficient and environmentally friendly power generation technology that generates electrical energy from hydrogen gas, natural gas and other renewable fuel. The implementation of SOFCs is still facing challenges because their performance needs to be improved. Constructing cells with solid material alone is difficult because good electrical contacts between the components must be maintained. The concept of a dual composite cathode is important for the development of SOFC single cells. Introducing dual composite cathode can create an ideal cathode microstructure that can improve phase contiguity and interfacial coherence. This paper reviews the behaviour of a perovskite-type oxide-based dual composite cathode of SOFC for the selection of suitable materials and the preparation of a dual composite cathode.